The Effect of AI Learning System on Student Learning Outcomes and Motivation - Agestiningrum, Restu; Siswanto, Siswanto (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2024)
This study examines the role of Islamic education in the development of AI, with a particular emphasis on how artificial intelligence affects students' religious understanding and learning process. This research aims to find out how the use of artificial intelligence impacts Islamic education and understand how this technology affects students' learning experiences. The research method used is experimental with a quantitative approach to determine how independent variables (treatments or treatments) affect dependent variables (outcomes) under controlled conditions. The conditions are controlled so that no other variables affect the dependent variable. The results show that artificial intelligence has the ability to expand students' access to Islamic education materials, offer customized learning, and help assess how far students understand religion. AI can also help people talk and interact more deeply about religious issues. But the use of AI in Islamic education raises moral issues such as privacy and data reliability. In conclusion, artificial intelligence has a lot of potential to enrich Islamic education, but it should be used carefully to avoid negative effects and maximize benefits and improve students' religious comprehension.